2015
DOI: 10.1245/s10434-015-4977-2
|View full text |Cite
|
Sign up to set email alerts
|

Transanal Endoscopic Microsurgery (TEM) Following Neoadjuvant Chemoradiation for Rectal Cancer: Outcomes of Salvage Resection for Local Recurrence

Abstract: Salvage resection for local recurrence following CRT and TEM is associated with high rates of R1 resection (CRM+) and local re-recurrence. Immediate completion of TME should be considered for patients with unfavorable pathological features after TEM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 22 publications
0
57
3
4
Order By: Relevance
“…The Brazil study [4] was the first to propose that nonoperation management could be used for patients with cCR. The Brazil study series [3, 4, 38, 39] also improved the process for nonoperation management, including patient selection, how and when to identify cCR, follow-up schedule, and salvage treatment. In the present study, we found that there is no difference in long-term survival, as measured by DM, DFS, and OS, in patients with cCR treated with a wait-and-see strategy compared to those with pCR who underwent radical surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The Brazil study [4] was the first to propose that nonoperation management could be used for patients with cCR. The Brazil study series [3, 4, 38, 39] also improved the process for nonoperation management, including patient selection, how and when to identify cCR, follow-up schedule, and salvage treatment. In the present study, we found that there is no difference in long-term survival, as measured by DM, DFS, and OS, in patients with cCR treated with a wait-and-see strategy compared to those with pCR who underwent radical surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In our previously reported oncological outcomes of TEM following nCRT, nearly all recurrences (89%) had residual cancer within the rectal wall. In fact, only 25% of patients with recurrent cancer had lymph node metastases in the resected specimen after salvage [10]. These findings are in contrast with the idea that local recurrences after local excision are exclusively within the mesorectum.…”
Section: Discussionmentioning
confidence: 76%
“…This suggests that MRI has a role not only for the diagnosis but also for surgical planning of these patients as indicated in previous studies for primary non-recurrent rectal cancer [21][22][23][24]. This is particularly relevant in a setting where R1 resections occur very frequently [10]. Ultimately, the suggestion of MRF +ve in MRI in these patients may lead surgeons to consider more extensive resections, even beyond the mesorectal plane.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, in another report from the same group, with an expanded series of 53 patients with NCCR after CRT for LARC, the 2-year LR rate after TEM was 22% (12/53 patients); nine of the patients were LR exclusively, and eight were deemed resectable by preoperative imaging and were operated with salvage intention. 32 Of note, a disappointing positive circumferential margin was obtained in most of the cases (7/8). The authors acknowledge that TME after LE might not be the best approach and make a call for completion TME immediately after TEM in the presence of bad pathological features (ypT2-3, LVI, perineural invasion, or poor differentiation).…”
Section: What Is the Role Of Local Excision For Nccr?mentioning
confidence: 90%
“…In fact, in the aforementioned study, 7 of 8 patients requiring a TME after LE required an abdominoperineal resection. 32 Several series have reported the results of a treatment protocol for rectal cancer patients treated according to a protocol consisting on CRT followed by LE, followed by immediate TME for patients found to have high-risk features (i.e., positive margins, LVI, perineural invasion, and poor differentiation) in the LE specimen. An Italian multicenter phase II study, including 63 patients with cT2/T3 tumor with a significant response to CRT and found to have ypT2, positive margins, tumor regression grade !…”
Section: What Is the Role Of Local Excision For Nccr?mentioning
confidence: 99%